Impact of hepatic rearterialization on reperfusion injury and outcome after mouse liver transplantation. - Steger, U; Sawitzki, B; Gassel, A; Gassel, H; Wood, K (2003)
BACKGROUND: Nonarterialized mouse liver transplantation is a well-established model for immunologic studies on rejection and tolerance mechanisms. However, the importance of graft arterialization has-in contrast to rat liver transplantation-not been thoroughly examined in the mouse model. The aim of the current study was to investigate the impact of arterial reconstruction on long-term graft survival, histologic alterations, ischemic liver damage, and early immunologic activation pathways. METHODS AND RESULTS: All recipients of arterialized (n=6) and nonarterialized (n=8) syngeneic liver grafts survived indefinitely. There were no differences in their histologic architecture, including no evidence of bile duct proliferation, periductal fibrosis, or alterations in serum transaminases, in long-term survivors from either group. Twenty-four hours after syngeneic liver transplantation, aspartate aminotransferase and alanine aminotransferase levels were increased to an equivalent extent in both groups, in agreement with early reperfusion injury and solitary traumatic injuries as assessed histologically (n=3 per group). Visualized by immunohistochemistry, intercellular adhesion molecule-1 expression was increased on sinusoidal and hepatic vein endothelium at both 1 and 100 days after transplantation, in both arterialized and nonarterialized grafts. Messenger RNA for interleukin-1, interferon-gamma, and tumor necrosis factor-alpha were measured by real-time polymerase chain reaction 24 hr after transplantation. No significant changes in the expression of cytokine mRNA levels were observed. CONCLUSIONS: Arterialization of mouse liver grafts does not appear to have a major impact on survival rate or the degree of immunologic activation. Therefore, the value of arterial reconstruction in mouse liver transplantation for experimental investigations is negligible.